2021
DOI: 10.3389/fcell.2021.664609
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of c-Jun/AP-1-Activity by the Cell Cycle Inhibitor p57Kip2

Abstract: p57 is a member of the Cip/Kip family of cell cycle inhibitors which restrict the eukaryotic cell cycle by binding to and inhibiting cyclin/CDK complexes. They are considered as tumor suppressors and inactivating genomic mutations of p57 are associated with human overgrowth disorders. Increasing evidence suggests that p57 controls additional cellular processes beyond cell cycle control such as apoptosis, cell migration or transcription. Here we report that p57 can stimulate AP-1 promotor activity. While transa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Phosphorylation of p27 Kip1 at T157 and T198 in PI3K‐hyperactivated cancers has been shown to drive p27 Kip1 binding to Janus kinase 2 (JAK2) and separately, it was demonstrated that this phosphorylated form of p27 Kip1 can bind and transcriptionally co‐activate c‐Jun. Interestingly, the related p57 kip2 has also been shown to exert transcriptional co‐regulatory activity [59], including the regulation of c‐Jun [60].…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of p27 Kip1 at T157 and T198 in PI3K‐hyperactivated cancers has been shown to drive p27 Kip1 binding to Janus kinase 2 (JAK2) and separately, it was demonstrated that this phosphorylated form of p27 Kip1 can bind and transcriptionally co‐activate c‐Jun. Interestingly, the related p57 kip2 has also been shown to exert transcriptional co‐regulatory activity [59], including the regulation of c‐Jun [60].…”
Section: Discussionmentioning
confidence: 99%
“…p57 may also control transcription by regulating RNA Polymerase II C-terminal domain (CTD) phosphorylation in an E2F1-dependent manner [54]. More recently, p57 was found to promote c-Jun and FHL2 mediated transcription by competing with HDAC1 and HDAC3 for binding to these transcription factors, thereby relieving their inhibition by HDACs [55, 56]. Interestingly, while the N-terminus of p57 acted as a transactivator, presumably by competing with HDACs, the C-terminus of p57 repressed c-Jun activity, suggesting a complex regulation that may depend on the binding partners of p57 and/or on posttranslational modifications [55].…”
Section: Discussionmentioning
confidence: 99%
“…COX-derived prostanoids appear to be involved in the pathogenesis of diabetic nephropathy (41), and a recent study regarded prostaglandins as potential targets for the treatment of polycystic kidney disease (42). JUN is a positive regulator of cell proliferation which promotes cell proliferation by accelerating G1-S cell cycle progression (43)(44)(45). It could bind with FOS to form AP-1 (Activator protein-1) early transcription response factor and mediate many biological functions (46,47).…”
Section: Discussionmentioning
confidence: 99%